ANALYSIS OF WEED VEGETATION ON PLANTATIONS KENAF (Hibiscus cannabinuS L.) IN DLIMAS, CEPER, KLATEN, CENTRAL JAVA - Ahmad Nur Rohim; Dwi Cahyo Budi Bhakti Bumi; Refido Arian Thohari (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2022)
Weed vegetation analysis is very necessary in controlling weeds in kenaf (Hibiscus cannabinus L.) plantations because weeds can compete in taking nutrients, water, sunlight, air, and growing space. A study on the analysis of weed vegetation in kenaf plantations was carried out in March 2022 in Dlimas Village, Ceper District, Klaten Regency, Central Java. This study aims to obtain the diversity of weed species and structures which include species, density, frequency, and weed dominance as the basis for proper, effective, and efficient control. The research was conducted by random sampling technique using the square method of 0.5 m x 0.5 m plot size with 3 replications. Furthermore, weeds in the sample plots were taken and identified using plantnet software to be matched with references. The results showed that there were 8 species of grass weeds, 3 species of tekian weeds, and 6 species of broadleaf weeds. Weeds found in kenaf plantations were dominated by broadleaf species. The three dominant weeds were Lindernia dubia L. Pennel (SDR 25,80 %), Eleusine indica L. Gaertn (SDR 8,90 %), and Phyllanthus urinaria (SDR 7,90 %).